Eye injuries sustained during protests due to non-lethal weaponry: a systematic review. (4th July 2021) - Liu, Winnie; Yu, Brian; Bursztyn, Lulu; Malvankar-Mehta, Monali S.
ABSTRACT: Introduction: Ocular injuries may be produced by non-lethal weaponry. With the upsurge of protests in the United States earlier in 2020, the consequences posed by non-lethal weaponry represent an emerging public health concern. This review summarizes the types of ocular injuries sustained, reports on secondary injuries when applicable and outlines the visual outcomes and necessary methods of treatments. Areas covered: This paper reviews the current literature pertaining to ocular injuries sustained during protests. The literature was searched through three databases (Medline, Ovid, CINAHL). Grey literature was searched through Clinical Trials.gov and ProQuest Dissertations and Theses. Conferences held through American Academy of Ophthalmology, Canadian Society of Ophthalmology, and Association for Research in Vision and Ophthalmology were searched. Primary studies that adhered to the inclusion and exclusion criteria were included. Expert opinion: Numerous forms of non-lethal weaponry are capable of producing ocular injuries. Open and closed globe injuries are observed in addition to countless secondary injuries. The presenting visual acuity is an indication to the severity of the ocular injuries. Surgical intervention is the frequent primary method of treatment. In the interest of public health, the necessary regulations must be implemented to control the usage of non-lethal weaponry during protests.